Features of Expert Evaluation of Investment Projects on the Example of the Medical Industry - S. P. Kovalev; E. R. Yashina; P. S. Turzin; K. E. Lukichev (Ekonomika Nauki)
The analysis of the normative legal documentation regulating the procedure for holding competitions for the best project is performed. The modern methodology and technology of selection and expert evaluation of investment projects in the state and commercial sectors of the economy are considered. The types of risks of ineffective management decisions are determined based on the analysis of the results of expert evaluation of these investment projects, including in the field of medicine.